Decreased intra-lymphocyte cytokines measurement in septic shock patients: A proof of concept study in whole blood. (April 2018) - Letessier, Wilfried; Demaret, Julie; Gossez, Morgane; Allam, Camille; Venet, Fabienne; Rimmelé, Thomas; Monneret, Guillaume
Highlights: Functional testing is the gold standard for monitoring immune status in clinics. New whole blood protocol for lymphocyte intracellular cytokine is available. We concomitantly assessed IFN-γ, IL-2, TNF-α levels in CD3/CD4 and CD3/CD8T cells in sepsis. This shows the potential of this flow cytometry protocol for clinical applications. Abstract: Functional testing protocols are thought to be the gold standard for the exploration of the immune system. However, in terms of routine analysis, they present numerous drawbacks and consequently their use is mainly limited to research applications. In the clinical context of septic shock, characterized by marked lymphocyte alterations, a new approach for lymphocyte intracellular cytokine measurement in whole blood upon was evaluated in a proof-of-concept study. Following lymphocyte activation, simultaneous intracellular labeling of Interferon-γ (IFN-γ), Tumor Necrosis Factor-α (TNF-α), and Interleukin-2 (IL-2) was performed in CD4 + and CD8 + T cells (identified by surface marking). The analysis was carried out by flow cytometry (6 colors). Results obtained in septic patients (n = 22) were compared to those of healthy volunteers (n = 8). Independently of lymphopenia, there were significant differences between groups. In particular there was significant decrease in the production of IL-2 and TNF-α in septic patients, while the production of IFN-γ was not significantly altered. Polyfunctional results showed that patients presented with increased percentages of triple negative lymphocytes. In contrast, volunteers had higher proportions of triple positive cells. The approach could be performed in a robust and consistent way, taking 4.5 h to complete. Moreover, clear differences could be observed between clinical groups with this modified method. These characteristics illustrate the potential of this novel whole blood protocol for clinical applications. However, further research is required to determine the applicability compared to alternative test and to evaluate clinical performances in larger cohorts of patients.